Pengaruh Modal Sendiri, Kredit Usaha Rakyat (KUR), dan Tenaga Kerja Terhadap Pendapatan UMKM di Kecamatan Batuan - Ila, Kholifatul; Andrianingsih, Very (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a sector that plays a significant role in driving Indonesia's economic growth. They are also considered a key force in strengthening economic resilience. The purpose of this study is to analyze the relationship between equity, micro-enterprise credit (KUR), and labor on MSME income in Batuan District. This study employed a quantitative method with a descriptive approach. The data used were primary data obtained through questionnaires distributed to MSMEs in Batuan District. The population of this study was 176 MSMEs, using a non-probability purposive sampling technique to obtain a sample of 82 respondents. Data management was performed using IBM SPSS 26. The results of this study indicate that the three independent variables, equity, micro-enterprise credit (KUR), and labor, both separately and simultaneously, significantly influence MSME income in Batuan District